The role of fibroblast-neutrophil crosstalk in the pathogenesis of inflammatory diseases: a multi-tissue perspective - Cai, Chen; Guan, Lanxi; Wang, Chenhao; Hu, Runjie; Ou, Lingling; Jiang, Qianzhou (Frontiers in Immunology, 2025)
Neutrophil-fibroblast crosstalk drives inflammatory pathology across organ systems through both shared and tissue-specific mechanisms. This review synthesizes evidence from skin, lung, gut, cardiovascular, joint, sinus, and oral diseases, revealing conserved molecular pathways where fibroblasts secrete chemokines (CXCL1/8/12) to recruit neutrophils, which, in turn, release neutrophil extracellular traps (NETs), elastase, and cytokines to modulate fibroblast function. Additionally, we identify critical tissue-specific differences, including the predominance of IL-36 signaling in COPD, IL-17-carrying NETs in systemic lupus erythematosus (SLE) and pulmonary fibrosis, and specialized fibroblast subpopulations, such as IDO1+ cells in CRSwNP and TNFRSF21+ cells in periodontitis. Translational insights highlight the therapeutic potential of targeting IL-17, NETs, and fibroblast subpopulations, though tissue-specific risks necessitate precision strategies. Future therapeutic efforts should focus on developing precision-targeted interventions that address organ-specific mechanisms to overcome treatment resistance in inflammatory disorders.